Counterproductive Effects of Rice For Poor (Raskin) Program on Labor Supply - Eka Riski Ningtiyas (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2018)
This study aims to examine the existence of the counterproductive effects of Rice For Poor (Raskin) program on labor supply. The impact evaluation is done by a combination of Difference-in-Difference and Propensity Score Matching methods. The estimation results have shown that Raskin has a significant impact on decreasing of households head working hours, especially on male. Based on these findings, it can be concluded that Raskin has a counterproductive effect on labor supply, but there is no evidence to say Raskin makes people lazy.